The Artistic Precariat: Commodification and Counter-Movements - Marques, J.S. (14th Conference of the European Sociological Association, 2019)
The paper investigates the formation of an ‘artistic precariat’ in Portugal and Brazil, through the analysis of the double movement of work commodification in the artistic sector and the struggles for decommodification through different dynamics of collective organization and action, inspired by Polanyi’s seminal work (1944) and by Wright’s emancipatory social science (2010). The research design involved the comparative analysis of theatre collectives in Portugal and Brazil based on historical, statistical and documentary sources in order to contextualize the artistic work in both countries; conducting a survey of theatre collectives in order to map their working conditions, organizational structure and collective action dynamics; interviews and participant observation to deepen two empirical cases. The research results corroborate the literature that highlights the artistic work as precursor of contemporary forms of work hyper-flexibilization. However, despite their strong precariousness and lack of representation in traditional forms of workers’ collective organization (unions), the research has also identified multiple resistances among artist-workers who envisage other forms of collective action and utopian visions for making a better world. On the one hand, the counter-movements of the artistic precariat are restrained by the submission of national regimes to the constraints of global capitalism. On the other hand, it is possible to observe experiences where they join forces in their social struggles that perhaps are not enough to make a new ‘great transformation’, but contain elements of resistance with a transformative potential.